2003
DOI: 10.1086/377354
|View full text |Cite
|
Sign up to set email alerts
|

Electron Collisional Excitation Rates for O i Using the B ‐Spline R ‐Matrix Approach

Abstract: The B-spline R-matrix approach has been used to calculate electron collisional excitation strengths and rates for transitions between the 3 P, 1 D, and 1 S states of ground configuration and from these states to the states of the excited 2s 2 2p 3 ns (n ¼ 3 5), 2s 2 2p 3 np (n ¼ 3 4), 2s 2 2p 3 nd (n ¼ 3 4), 2s 2 2p 3 4f , and 2s2p 5 configurations. The nonorthogonal orbitals are used for an accurate description of both the target wave functions and the R-matrix basis functions. The thermally averaged collisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…The rates are about a factor of five and two greater than ours, respectively. Zatsarinny & Tayal (2003) have published effective collision strengths based on calculations using the B-spline R-matrix approach with non-orthogonal orbitals. They provide data for transitions between the 3 P, 1 D, and 1 S states of the ground configuration and from these states to 23 other excited states.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rates are about a factor of five and two greater than ours, respectively. Zatsarinny & Tayal (2003) have published effective collision strengths based on calculations using the B-spline R-matrix approach with non-orthogonal orbitals. They provide data for transitions between the 3 P, 1 D, and 1 S states of the ground configuration and from these states to 23 other excited states.…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps the best estimate of the error is obtained from the scatter among different R-matrix calculations where available. From the comparison with the rates of Zatsarinny & Tayal (2003) and the rates of Berrington & Burke (1981), we would estimate that the rate coefficients have errors of the order of 70% at the temperatures of interest. It is difficult to predict the impact that these new data will have on the results of non-LTE calculations in stellar atmospheres.…”
Section: Resultsmentioning
confidence: 99%
“…We took the relative abundance of C + and O to be the solarsystem C/O ratio, 0.46 (Lodders & Palme 2009). We used the collision strengths computed by Bell et al (1998) and Zatsarinny & Tayal (2003) for e−O, and by Tayal (2008) The observed line ratios give an electron density of n e ∼10 4 cm −3 and T = 130 K for the extended emission component (see Figure 4), appropriate for PDRs with incident FUV field strength of G 0 ∼ 100 (Kaufman et al 1999). The values for n e , T and G 0 that we obtain lie in the ranges commonly observed for PDRs on the surface of molecular clouds (Hollenbach & Tielens 1997, indicating that the extended component surrounding the jet is consistent with the emission from a photodissociation region (PDR) on the surface of the OMC-2 cloud.…”
Section: Extended Pdr Emission In Omc-2mentioning
confidence: 99%
“…As indicated in Table 14, we adopt the values given by Zatsarinny & Tayal (2003) for the transitions they include and those of Bhatia et al (1982) for the additional transitions that they list. Otherwise, we use the Seaton and van Regemorter formulae for radiative and nonradiative transitions, respectively.…”
Section: O I Collisional Excitationmentioning
confidence: 99%